Conscientious Objection Before the Indonesian Constitutional Court - Heribertus Jaka Triyana (The Constitutional Court of the Republic of Indonesia, 2022)
The issuance of Indonesia’s Law No. 23 of 2019 on the Management of National Resources for State Defense (PSDN Law) sparked a national debate on conscription and conscientious objection. Consequently, a coalition of civic society organizations submitted the PSDN Law before the Constitutional Court for judicial review. They argued that the PSDN Law violates the Indonesian Constitution’s Article 28 on human rights protection. One of the legal submissions is based on the argument that the PSDN Law deliberately ignores human rights in order to provide reserve and backup components to the military. This argument is supported by Article 18 of the International Covenant on Civil and Political Rights (ICCPR) and the ICCPR’s General Comment No. 22 of 1993 paragraph 11, justifying conscientious objection as an inherent human right. The analysis in this paper is mainly uses the legal positivism paradigm and the human rights-based approach. This paradigm provides a framework for analyzing how the PSDN Law generates a distinctive legal feature for Indonesia’s legal system. In line with Article 28 of the Indonesian Constitution, the Constitutional Court should explicitly assess the preservation of civil rights. It may be claimed that conceivable legal gaps (norm versus reality) and legal loopholes add to the Constitutional Court’s obligation to consider the omission of conscientious objection recognition. This article argues the Constitutional Court should adjudicate on the issue of citizens being conscripted as reserve and backup components in situations of military threats, hybrid threats and/or non-military threats. This research further maintains that the Constitutional Court should recognize the existence of conscientious objection as an inherent human right, as a form of judicial activism. In accordance with the doctrine of judicial activism, the Court could resolve and offer solutions to the existence of conscientious objection as a democratic civil right. The Court should also determine the area, scope, application and orientation of conscientious objection as a distinct feature of human rights based on Indonesia’s context and perspective on defense required by international human rights treaties, conventions, or general comments on such instruments.